Distance to food stores & adolescent male fruit and vegetable consumption: mediation effects - Jago, Russell (BioMed Central, 2007)
BACKGROUND: The physical environments in which adolescents reside and their access to food stores may influence their consumption of fruit and vegetables. This association could either be direct or mediated via psychosocial variables or home availability of fruit and vegetables. A greater understanding of these associations would aide the design of new interventions. The purpose of this study was to examine associations between distance to food stores and restaurants and fruit and vegetable consumption and the possible mediating role of psychosocial variables and home availability. METHODS: Fruit and vegetable consumption of 204 Boy Scouts was assessed by a food frequency questionnaire in 2003. Participant addresses were geo-coded and distance to different types of food stores and restaurants calculated. Fruit and vegetable preferences, home availability and self-efficacy were measured. Regression models were run with backward deletion of non-significant environmental and psychosocial variables. Mediation tests were performed. RESULTS: Residing further away from a small food store (SFS) (convenience store and drug store) was associated with increased fruit and juice and low fat vegetable consumption. Residing closer to a fast food restaurant was associated with increased high fat vegetable and fruit and juice consumption. Vegetable preferences partially mediated (26%) the relationship between low fat vegetable consumption and distance to the nearest SFS. CONCLUSION: Distance to SFS and fast food restaurants were associated with fruit and vegetable consumption among male adolescents. Vegetable preferences partially mediated the distance to low fat vegetable relationship. More research is needed to elucidate how environmental variables impact children's dietary intake.